Global Causes of Diarrheal Disease Mortality in Children <5 Years of Age: A Systematic Review - Lanata, Claudio F.; Fischer-Walker, Christa L.; Olascoaga, Ana C.; Torres, Carla X.; Aryee, Martin J.; Black, Robert E. (PloS one, 2013)
Estimation of pathogen-specific causes of child diarrhea deaths is needed to guide vaccine development and other prevention strategies. We did a systematic review of articles published between 1990 and 2011 reporting at least one of 13 pathogens in children <5 years of age hospitalized with diarrhea. We included 2011 rotavirus data from the Rotavirus Surveillance Network coordinated by WHO. We excluded studies conducted during diarrhea outbreaks that did not discriminate between inpatient and outpatient cases, reporting nosocomial infections, those conducted in special populations, not done with adequate methods, and rotavirus studies in countries where the rotavirus vaccine was used. Age-adjusted median proportions for each pathogen were calculated and applied to 712 000 deaths due to diarrhea in children under 5 years for 2011, assuming that those observed among children hospitalized for diarrhea represent those causing child diarrhea deaths. 163 articles and WHO studies done in 31 countries were selected representing 286 inpatient studies. Studies seeking only one pathogen found higher proportions for some pathogens than studies seeking multiple pathogens (e.g. 39% rotavirus in 180 single-pathogen studies vs. 20% in 24 studies with 5-13 pathogens, p<0.0001). The percentage of episodes for which no pathogen could be identified was estimated to be 34%; the total of all age-adjusted percentages for pathogens and no-pathogen cases was 138%. Adjusting all proportions, including unknowns, to add to 100%, we estimated that rotavirus caused 197 000 [Uncertainty range (UR) 110 000-295 000], enteropathogenic E. coli 79 000 (UR 31 000-146 000), calicivirus 71 000 (UR 39 000-113 000), and enterotoxigenic E. coli 42 000 (UR 20 000-76 000) deaths. Rotavirus, calicivirus, enteropathogenic and enterotoxigenic E. coli cause more than half of all diarrheal deaths in children <5 years in the world.